To study the Financial Performance of top five privatized Banks in India With special reference to( HDFC, AXIS, ICICI, KMB, IndusInd Bank) - ANNU; KUMAR, SUSHIL; TRIPATHI, DR. RAVINDRA (The journal of contemporary issues in business and government, 2021)
The purpose of this research is to assess the performance of the top-five private sector banks in India from 2016 to 2021. The goal is also to investigate the profitability of these selected banks during covid-19. Approach/Methodology/Design: The study sample consisted of five private banks. The study used statistical tools such as the Minimum and Maximum Net Profit Ratio, Descriptive Statistics, and the One-Way ANOVA test to evaluate bank performance. The study spans the years 2016- 17 to 2020-21 and it is entirely based on secondary data. Findings: The study’s findings demonstrate that the Net Profit of the selected banks differs significantly. Due to the significant profit earned and the efficient management that is applied, HDFC Bank’s &Kotak Mahindra Bank financial performance is consistently good. Because to governance concerns, misleading guarantee to consumers, non-serious investors, no market-led resurgence in sight, outflow of liquidity, and non-disclosure practices, the results show that INDUSIND Bank’s financial position is deteriorating. Axis Bank and INDUSIND Bank are gradually losing market share. Practical Implications: In today’s environment, most banks have a higher percentage of nonperforming assets. As a result of this situation, numerous banks are considering liquidation or mergers and acquisitions. This article aims to investigate the current state of selected private sector banks in India, assisting in the presentation of statistical analysis that will be useful to both investors and bank management teams. Originality/value: Banks are now one of the fastest expanding industries, with large sums of money being invested in them. The banking system is getting increasingly complicated, necessitating a greater requirement to assess bank performance.